Degradation Level and Wetland Rice Rehabilitation Effort in Medan Krio Village Sunggal District Deli Serdang - Mhd Zakaria (International Journal of Ecophysiology, 2020)
The purposes of this research are to know the level of paddy field degradation, mapping level of paddy field degradation and analyze effort of paddy field rehabilitation in Beringin Subdistrict of Deli Serdang Regency of North Sumatera Indonesia to increase rice productivity. This research was conducted in Medan Krio Village, District Sunggal Regency Deli Serdang of North Sumatera. The study was conducted in March to July 2017. This research used nonfactorial Randomized Block Design (RBD) with 5 levels organic dosage treatment of Compost Waste City, i.e: B0: Control, B1: Dose 1.5% (36,00 ton/ha), B2: Dose 3% (72,00 ton/ha), B3: Dose 4.5% (108,00 ton/ha), B4: Dose 6% (144,0 ton/ha). The parameters that will be analyzed are the physical, chemical and biological properties of soil in paddy fields. The result showed, treatment with Dose 6% (B4) can (1) improve physical properties of soil Bulk Density, Porosity and the effective depth of soil; (2) increase the C-organic content, N-Total levels of P-Available, CEC soil, and low C/N Ratio; (3) increase Soil organic matter and total Microbes. So, Treatment Dose 6% (B4) of compost waste city gives the best effect to the physical, chemical and biological properties of soil in paddy fields